2019
DOI: 10.1093/database/baz027
|View full text |Cite
|
Sign up to set email alerts
|

SELER: a database of super-enhancer-associated lncRNA- directed transcriptional regulation in human cancers

Abstract: Super-enhancers (SEs) are enriched with a cluster of mediator binding sites, which are major contributors to cell-type-specific gene expression. Currently, a large quantity of long non-coding RNAs has been found to be transcribed from or to interact with SEs, which constitute super-enhancer associated long non-coding RNAs (SE-lncRNAs). These SE-lncRNAs play essential roles in transcriptional regulation through controlling SEs activity to regulate a broad range of physiological and pathological processes, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…In addition, seRNAs can be divided into cis-acting and trans-acting seRNA according to distinct function approaches ( Fig. 2a, b) [18]. Cis-acting seRNA recruits protein complexes from its synthetic site to activate adjacent genes, where the whole length or TSS of cis-acting seRNA is covered by SE [10].…”
Section: Serna's Characteristics and Its Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, seRNAs can be divided into cis-acting and trans-acting seRNA according to distinct function approaches ( Fig. 2a, b) [18]. Cis-acting seRNA recruits protein complexes from its synthetic site to activate adjacent genes, where the whole length or TSS of cis-acting seRNA is covered by SE [10].…”
Section: Serna's Characteristics and Its Functionsmentioning
confidence: 99%
“…DNA translocations, small insertions and deletions (indels), focal amplification, singlenucleotide polymorphisms (SNPs), TFs implication and viral infections mediate aberrant SE generation, and the SE further transcribes into seRNA [15][16][17]. The recent studies have discovered two types of seRNA, cis-acting and transacting seRNA [18]. Meanwhile, according to different transcriptional directions, seRNA is defined as 1d-and 2d-seRNA [19].…”
Section: Introductionmentioning
confidence: 99%
“…Driver genes are collected on March 23 rd 2018. The cis-acting differentially expressed super-enhancer associated lncRNAs for different cancers are retrieved from the SELER database [20] (June 23 th 2019).…”
Section: Data Sources and Data Processingmentioning
confidence: 99%
“…Super-enhancers are groups of putative enhancers that are spatially proximal to the mediator binding sites [48]. They regulate gene expression by increasing the gene transcription [20]. Disease-related variations occur in the super-enhancer regions.…”
Section: Inferring Functional Mechanisms For the Super-enhancer Assocmentioning
confidence: 99%
“…Recent studies have revealed that SE-lncRNAs are usually emerging as master RNA regulators in diverse gene expression programs and activate the gene expression by mechanisms of transcription factor trapping, chromatin looping, chromatin modi cation, PolII loading, and release of transcriptional repressor [7][8][9][10][11]. SE-lncRNAs are intimately involved in regulating tumorigenesis [11,12]. A good example is that CCAT1-L positively regulates MYC expression by mediating chromatin looping between the MYC promoter and its enhancers to promote CRC progression [11].…”
mentioning
confidence: 99%